Pengembangan Mobile Learning Berbasis Android Pada Mata Kuliah Strategi Pembelajaran Universitas Baturaja - Sulia Ningsih; Anita Adesti (Edcomtech: Jurnal Kajian Teknologi Pendidikan, 2019)
The development of science and technology, especially in the field of information technology and communication, has provided a breath of fresh air in improving the quality of education. The use of android smartphones by students as a communication medium is one of the potentials that can be developed to support virtual mobile learning in universiy. This studywas aimed at (1) developing android-based mobile learning and (2) testing the feasibility of android-based mobile learning in learning strategy courses with valid and practical criteria. This research and development study used a procedural development model adapted from the Pustekom development model according to Warsita which includes (1) the planning stage, (2) the stage of media production or development, and (3) the evaluation or evaluation stage product. The results of the study showed that (1) Android-based mobile learning applications were produced in learning strategy courses, (2) Android-based mobile learning was proper to use in learning strategy course. This was in accordance with the results of the material expert validation test (83.28 = valid), learning design experts (83.5 = valid) and media experts (81,31 = valid), individual evaluation (85.45 = practical), evaluation small group (85.83 = practical), and field trials (85.84 = practical).